IDENTIFICATION OF STUDENTS' TECHNO-MATHEMATICAL LITERACIES (TML) ABILITIES: PRELIMINARY RESEARCH - Himmi, Nailul; Saragih, Sahat; Hasratuddin (MATEMATIKA DAN PEMBELAJARAN, 2024)
The development of digital technology has changed the way humans interact with mathematical information, making Techno-Mathematical Literacies (TML) increasingly crucial in the digital era. The research aims to identify and analyze the TML abilities of students as an initial step in understanding the TML ability profile at the higher education level. The research uses a mixed-method approach with an explanatory sequential design. 31 students from the Civil Engineering program at the University of Riau Islands, selected as research subjects, were chosen using the purposive sampling technique. Data collection used the TML ability test with four dimensions. The content validity score was 0.85 using Aiken's V formula, followed by semi-structured interviews with 6 students. The research results show that the average TML ability of the students is in the low category (35.53%). The analysis of TML components reveals that students perform best in digital mathematical representation (42.78%), digital mathematical literacy (37.08%), digital mathematical validation (34.79%), and have the lowest ability in using mathematical software (24.58%). Thematic analysis identified four main factors influencing the development of TML: the process of technology integration, technical and adaptation barriers, the development of problem-solving skills, and perceptions and attitudes towards TML. These findings imply the need for more intensive and structured learning interventions to enhance students' TML skills, particularly in the aspect of mastering mathematical software. The recommended strategies include a project-based approach and the use of various innovative digital media. Keywords: Higher Education; Mathematics Learning; Premilinary Research; Techno-Mathematical Literacies; Technology Integration